A qualitative evaluation of the specific carbohydrate diet for juvenile idiopathic arthritis based on children's and parents' experiences - Naima Hagström; Elin Lövestam; Afsaneh Koochek; Lillemor Berntson (BMC, 2023)
Abstract Background Insights into the immunological role of the gastrointestinal tract in autoimmune conditions have led to the investigation of diet as a potential adjunctive treatment option for juvenile idiopathic arthritis (JIA). The specific carbohydrate diet (SCD) has shown promising results. However, studies on participants' experiences of dietary interventions in JIA are rare. In this study we investigated the experiences of children and parents' who had participated in a four-week intervention with SCD aiming to examine the potential anti-inflammatory effects. Objectives To conduct a qualitative evaluation exploring children's and parents' experiences of the dietary intervention, how they navigated challenges, and their support requirements. Methods Semi-structured interviews were conducted with 12 children and 15 parents from 13 families, who were interviewed individually and together. The transcripts were analysed using systematic text condensation. Results Most participants interviewed found the intervention beneficial, with 12 out of 13 reporting positive effects, such as reduced pain and morning stiffness, and improved gastrointestinal function. Many participants reported being willing to repeat the intervention in the current form. Despite facing challenges, all children followed the diet for one to three months, with some continuing to follow a modified version. Facing the socio-emotional consequences of adhering to the diet was challenging for children. These were handled by focusing on the positive aspects and by relying on the supportive environment available. Parents struggled with practical issues since the diet required hard work, time, and money. Areas identified as requiring additional support include finding simple, quick, and child-friendly solutions, strengthening organizational food skills such as meal planning, and preparation prior to starting the intervention regarding socio-emotional aspects. Conclusion Navigating the dietary treatment was considered challenging, practically for the parents and socio-emotionally for the children. Based on the reported challenges and participants' suggestions the intervention could be optimised by providing support and solutions in relation to the practical issues and better preparation regarding dealing with the socio-emotional consequences. Despite the difficulties, the participants reported overall positive experiences of, and attitudes towards, the current setup. Consequently, dietary interventions, such as the SCD, may be regarded as suitable targets for further research.